On limits of Wireless Communications in a Fading Environment: a General Parameterization Quantifying Performance in Fading Channel - Amit Grover; Neeti Grover (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2014)
The reliable services along with high throughput can be achieved by using wireless communication systems. These systems also provides a wide coverage because of their features, no doubt MIMO Communication System [1] is one among them. Features provided by these systems ensure the improved system coverage and increased data transmission rate by considering multiple numbers of transmitter and receiver antennas. In this article, the concept of equalization has been considered and finally the performance of the MIMO Systems in Rician flat fading [5] channel is compared with the Rayleigh flat fading channel. It has also been observed that the performance of these Systems in Rician Flat Fading Channel is the best as compare to the Rayleigh Flat Fading Channel [10]. It has been concluded that the successive interference methods provide better performance as compare to others, but their complexity is high. Simulation results shows that ML provides the better performance in comparison to other equalizers but Sphere decoder provides the best performance.